Geopolitics and new actors of Latin American integration (2020)
We can differentiate diverse Latin Americas with vulnerabilities, sensitivities and very varied developments. In them, the State and other non-governmental actors interact depending on the opening of the political regime, as well as the economic and political elites. Countries, like the United States, which have exercised a unipolar hegemony in the region, undergo a weakening and begin to be replaced by others such as China or the European Union. Leaderships begin to be questioned; new candidates want to enter the race, such as Venezuela and Colombia, although they tend to be isolated from the regional and international scene. The presidential, regional and local elections of the last two years have altered the integration processes. The Pink Wave was replaced by neoliberal governments, and there is talk of a Latin America that tends to the “right”. This change marks new integrationist and fragmentary tendencies, and the dilemma of whether multilateral or bilateral is privileged. The role of the sovereign State and its autonomy is questioned; new emerging actors develop their foreign policies, often without regard to state structures. This parallel diplomacy affects regional organizations and their power can develop international actions. In this book we analyze general aspects that point to governance linked to issues such as democracy, environment, cooperation, and education, pointing out multiple crises at the global level and the international liberal order, which are reflected in the integrationist crossroads that crosses the region.